Polysaccharide food matrices for controlling the release, retention and perception of flavours. (June 2018) - Cook, Sarah L.; Methven, Lisa; Parker, Jane K.; Khutoryanskiy, Vitaliy V.
Abstract: Polysaccharides have many roles across both the food and pharmaceutics industries. They are commonly used to enhance viscosity, stabilise emulsions and to add bulk to food products. In the pharmaceutics industry, they are also utilised for their mucoadhesive nature. Mucoadhesive polysaccharides can facilitate retention of active ingredients at mucosal sites for a prolonged time and formulations can be designed to control their release and bioavailability. This study investigates how polysaccharides, with differing physicochemical properties (e.g. functional groups and molecular weight), affect the release and perception of flavour compounds from films. Polysaccharide films were prepared using either high or low viscosity carboxymethyl cellulose, pullulan or hydroxypropyl methylcellulose. Glucose, vanillin or a combination of both was also added to the films to assess the effect of flavour release and perception over time. The films were assessed for glucose release in vitro, swelling and disintegration times, and mucoadhesive ability. Results show that flavour release and perception depend on the polysaccharide matrix properties; this includes how quickly the films dissolve, the rate of release of tastant compounds, and the mucoadhesive strength of the polysaccharide. A higher viscosity and slower disintegration time resulted in slower release of glucose in vitro and flavour perception in vivo . Graphical abstract: Image 1 Highlights: Films made with mucoadhesive polysaccharides alter glucose release and perception. Glucose release depends on the viscosity and charge of the polysaccharide. Cross-modal interactions with congruent aroma alters temporal flavour perception.